Recombinant RXFP1-LDL-A module does not form dimers - Petrie, Emma J.; Periguini, Matthew A.; Bathgate, Ross A.D.; Gooley, Paul R. (Italian Journal of Anatomy and Embryology, 2014)
The Relaxin receptor, RXFP1, is a complex G-protein coupled receptor (GPCR). It has a rhodopsin- like 7 transmembrane helix region and a large ecto-domain containing Leucine-rich repeats and a Low Desnsity Lipoprotein Class-A module at the N-terminus. RXFP1 and the closely related receptor for INSL3, RXFP2 are the only mammalian GPCRs to contain an LDL-A module. The LDL-A module has been shown to be essential for receptor signal activation. RXFP1, like other GPCRs, has been shown to form dimers however the interface upon association is currently unknown. As LDL-A modules are commonly found as repeats we hypothesized that the LDL-A module may associate at the dimer interface and play a role in receptor activation. To this end we analyzed the ability for the LDL-A module to oligomerise via Analytical Ultracentrifugation (AUC).